Multiple calcifying hyperplastic dental follicles - Sonal Grover; George Koshy; Deepti Sharma; Bhushan Sharma (Wolters Kluwer Medknow Publications, 2017)
Hyperplastic dental follicles are very commonly seen associated with an impacted tooth. Multiple calcifying hyperplastic dental follicles (MCHDF), a term used for multiple unerupted teeth with abundant calcifications and rests of odontogenic epithelium in enlarged dental follicles is a rare entity. Varied pattern of calcifications have been observed in such follicles. We report one such case with four patterns of calcifications and odontogenic epithelium associated with bilaterally impacted canines.